The biogenesis of CLEL peptides involves several processing events in consecutive compartments of the secretory pathway - Stührwohldt, Nils; Scholl, Stefan; Lang, Lisa; Katzenberger, Julia; Schumacher, Karin; Schaller, Andreas (eLife, 2020)
Abstract Post-translationally modified peptides are involved in many aspects of plant growth and development. The maturation of these peptides from their larger precursors is still poorly understood. We show here that the biogenesis of CLEL6 and CLEL9 peptides in Arabidopsis thaliana requires a series of processing events in consecutive compartments of the secretory pathway. Following cleavage of the signal peptide upon entry into the endoplasmic reticulum (ER), the peptide precursors are processed in the cis-Golgi by the subtilase SBT6.1. SBT6.1-mediated cleavage within the variable domain allows for continued passage of the partially processed precursors through the secretory pathway, and for subsequent post-translational modifications including tyrosine sulfation and proline hydroxylation within, and proteolytic maturation after exit from the Golgi. Activation by subtilases including SBT3.8 in post-Golgi compartments depends on the N-terminal aspartate of the mature peptides. Our work highlights the complexity of post-translational precursor maturation allowing for stringent control of peptide biogenesis.
Gesehen am 12.05.2020